Media and Political Participation in Gombe State, Nigeria - Bello, Muhammad A.; Sule, Babayo (Kashere Journal of Politics and International Relations, 2024)
The aim of the study is to historicize the role of the media in promoting political participation in Gombe State since 1996, drawing insights from data obtained from interviews and documents. To this end, the study examined how the media has shaped democracy in Gombe since 1996. The findings from the interviews suggest that the effectiveness of the media in Nigeria in promoting democracy has been constrained by several factors. For this reason, Nigerian democracy has remained highly unstable since the return to the current form of democratic government. The study revealed that the development of media houses in Gombe has served to enlighten the local populace on political activities in the state. The media has therefore played the role of a watchdog for checks and balances between the government and the governed and for sensitizing the public through various programs. The paper examines the history of the media's role in promoting political participation, facilitating the free flow of information, and exploring and promoting accountability. It also examines the challenges the media has faced in achieving these goals, such as government censorship, lack of resources, and attacks on journalists. The study concludes with a critical assessment of the media's contribution to democracy and political participation in Gombe State since 1996 and its impact on the broader Nigerian democratic system. The methodology of data collection includes structured interviews and the use of secondary source material.